TYPE 1 DIABETES PATIENTS FOLLOW-UP IN DIABETES ONE-STOP CLINIC(DOSC) DURING COVID-19 PANDEMIC : SINGLE CENTRE EXPERIENCE IN PAHANG - Jasmiad, Nurbadriah Binti; Keong, See Chee; Ismail, Muizz Shafiq Bin Dato’ Shamsul (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Management of type 1 diabetes mellitus (T1 DM) patients in early adulthood is associated with unique challenges. COVID-19 pandemic had significantly impacted the quality of patient follow-up and access to care. This study assessed the characteristics of T1 DM patients under diabetes one-stop clinic (DOSC) follow-up in Hospital Sultan Haji Ahmad Shah (HoSHAS), Temerloh, Pahang and the impact of the pandemic on diabetes control. METHODOLOGY In this cross-sectional study, all T1 DM patients under active follow-up were recruited. Data regarding demographics, diabetes control and COVID-19 infection status were reviewed. Further analyses were performed by dividing them into 2 groups according to COVID-19 infection status: covid-19 positive (group 1) and COVID-19 negative (group 2). RESULTS Thirty T1 DM patients [60% female, 63.3% Malay ethnicity, mean age 24.4 (SD7.4) years, median weight 58.35 (IQR 10.3) kg, median disease duration 6.0 (IQR 8.0) years, mean duration under DOSC follow-up 4.1 (SD 1.6) years] were analysed. Incident retinopathy was seen in 10.0% of patients. Within the past 12 months, 26.7% had recent hospitalisation, majority due to diabetes ketoacidosis. Within the past 3 months, 13.3% had experienced hypoglycaemia. Mean HbA1c in T1 DM increased steadily from 2019 to 2020 and 2021 (8.87% vs 8.93% vs 9.35%). Thirteen T1 DM patients (46.4%) had COVID-19 infection between 2020 and 2022. Patients with COVID-19 infection had lower HbA1c than those not infected but it was not statistically significant (8.74% vs 9.07%, p=0.82). They also tended to have more microvascular complications. CONCLUSION COVID-19 pandemic had negatively impacted diabetes control in our cohort. There was also a high hospitalisation rate during this period. The HbA1c level was not associated with increased risk of COVID-19 infection in our cohort.